Metal Ion Release From Ni-Cr Alloy with Different Artificial Saliva Acidities - Amrah Y.Al-Jmmal (University of Mosul, College of Dentistry, 2014)
AIMS: evaluate the effects of changes in salivary pH on ion release from the Ni - Cr alloy at different time and calculate the amount of nickel, chromium ions released from these alloys. MATERIALS AND METHODS: Fourty eight specimens of Ni-Cr alloy were divided, four specimens immersed in each of four types of artificial saliva at different pH (7 as control,6,5 and 2.5), in three storage periods (12, 24 and 36 days). All test tubes were incubated at 37°C. After the immersion time was finished the quantities of metallic ions released for Ni and Cr were measured for each test solutions after 12, 24 and 36 days of immersion by atomic absorption spectroscopy. RESULT: The results of Nickel and Chromium ion release showed a statistically significant difference at p≤0.05 between three immersion solutions after (12, 24, 36) days, artificial saliva (pH2.5) showed higher rate of Ni and Cr release than artificial saliva (pH 7as control ,6,5) after various immersion times. It should mention the nickel ion release has been found to be more than chromium ion release. CONCLUSIONS: There is an evidence that the Ni and Cr ions release from Ni-Cr alloy at the presence of different acidity of artificial saliva. Chromium and nickel ion release in small amount in artificial saliva with pH(6,5), while in pH 2.5 release in large amount after (12, 24, 36) days of immersion. Nickel exhibited the highest level of ion release than Cr